Ruminant feeds in Malaysia - current status and constraints faced by industry - Wan Zahari Mohamed; Yunus I.; Shanmugavelu S. (2013)
In contact to the non-ruminant sub-sector, local ruminant industry is not well developed. Issues related to the feed supply are the attributing factors which limit ruminant production. Current emphasis is towards the development of practical and low-cost feeds for various classes of ruminant species. Low utilization of fibre resources, lack of practical techniques to convert local feedstuffs to quality feeds, low efficiency of collecting and harvesting of raw materials, high cost of drying of raw materials, inefficient storage and handling of forage based feeds and lack of established quality assurance protocols for prepared feeds are some of the limitations in the development of feeds for local ruminant livestock. Appropriate strategies to enhance rumen function and the means to administer supplements are of importance to ruminant feeding, as well as increase utilization of potential feed resources under the plantation environment. total mix tarions (TMR) and complete feeds are popular amongst the intensive feedloty operators, but to majority of smallholders, balance feeding is of less concerned. New approaches have to be utilized to improve the quality of the raw materials and finished products. Apart from making use of locally available ingredients to reduce cost of production, attempts have been made to produce more value-added feeds aiming at improve overall digestive system, growth performances and health status of the ruminants. There are less than 15 feed millers specializing in ruminants feeds throughout Malaysia and most are operated at minimum capacity (<2 tones per hour). Problems associated with ruminant feed production at the factory levels are discussed